Taxonomic studies on the genus Delphinium (Ranunculaceae) from China (XVI): Three new synonyms of D. lacostei - Li, Hui-Min; Yuan, Qiong; Yang, Qin-Er (Phytotaxa, 2018)
Delphinium taxkorganense, D. tetragynum and D. yechengense (Ranunculaceae) were all described from western Xinjiang, China. Critical observations on both herbarium specimens (including type material) and living plants demonstrate that they are indistinguishable from each other and are conspecific with D. lacostei. We therefore place them into the synonymy of D. lacostei, the earliest name.